Lessons Learned from Inherited Metabolic Disorders of Sulfur-Containing Amino Acids Metabolism - Kožich, Viktor; Stabler, Sally (The Journal of nutrition, 2020)
The metabolism of sulfur-containing amino acids (SAAs) requires an orchestrated interplay among several dozen enzymes and transporters, and an adequate dietary intake of methionine (Met), cysteine (Cys), and B vitamins. Known human genetic disorders are due to defects in Met demethylation, homocysteine (Hcy) remethylation, or cobalamin and folate metabolism, in Hcy transsulfuration, and Cys and hydrogen sulfide (H2S) catabolism. These disorders may manifest between the newborn period and late adulthood by a combination of neuropsychiatric abnormalities, thromboembolism, megaloblastic anemia, hepatopathy, myopathy, and bone and connective tissue abnormalities. Biochemical features include metabolite deficiencies (e.g. Met, S-adenosylmethionine (AdoMet), intermediates in 1-carbon metabolism, Cys, or glutathione) and/or their accumulation (e.g. S-adenosylhomocysteine, Hcy, H2S, or sulfite). Treatment should be started as early as possible and may include a low-protein/low-Met diet with Cys-enriched amino acid supplements, pharmacological doses of B vitamins, betaine to stimulate Hcy remethylation, the provision of N-acetylcysteine or AdoMet, or experimental approaches such as liver transplantation or enzyme replacement therapy. In several disorders, patients are exposed to long-term markedly elevated Met concentrations. Although these conditions may inform on Met toxicity, interpretation is difficult due to the presence of additional metabolic changes. Two disorders seem to exhibit Met-associated toxicity in the brain. An increased risk of demyelination in patients with Met adenosyltransferase I/III (MATI/III) deficiency due to biallelic mutations in the MATIA gene has been attributed to very high blood Met concentrations (typically >800 μmol/L) and possibly also to decreased liver AdoMet synthesis. An excessively high Met concentration in some patients with cystathionine β-synthase deficiency has been associated with encephalopathy and brain edema, and direct toxicity of Met has been postulated. In summary, studies in patients with various disorders of SAA metabolism showed complex metabolic changes with distant cellular consequences, most of which are not attributable to direct Met toxicity.
Keywords: játra; Homocystinuria; remethylation defects; ethylmalonic encephalopathy; Cysteine; Amino Acids, Sulfur; Humans; Metabolic Diseases; Brain Diseases; homocystinuria; homocystinurie; Metabolism, Inborn Errors; S-adenosylhomocysteine hydrolase deficiency; homocystein; lidé; zvířata; Methionine Adenosyltransferase; Homocysteine; cystathionine β-synthase deficiency; glycine N-methyltransferase deficiency; Methylation; cystein; Glutathione; adenosine kinase deficiency; nemoci mozku; siřičitany; Hydrogen Sulfide; methionine adenosyltransferase I/III deficiency; methionine restricted diet; Liver; metylace; metabolické nemoci; Sulfites; vrozené poruchy metabolismu; S-adenosylmethionin; Sulfur; glutathion; sloučeniny síry; S-Adenosylmethionine; sulfan; methionin; síra; Methionine; Animals; sulfite oxidase deficiency; aminokyseliny sírové; methioninadenosyltransferasa; Sulfur Compounds